2019
DOI: 10.1094/pdis-09-18-1622-re
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sorghum Enhanced in Monolignol Biosynthesis to Stalk Rot Pathogens

Abstract: To increase phenylpropanoid constituents and energy content in the versatile C4 grass sorghum (Sorghum bicolor [L.] Moench), sorghum genes for proteins related to monolignol biosynthesis were overexpressed: SbMyb60 (transcriptional activator), SbPAL (phenylalanine ammonia lyase), SbCCoAOMT (caffeoyl coenzyme A [CoA] 3-O-methyltransferase), Bmr2 (4-coumarate:CoA ligase), and SbC3H (coumaroyl shikimate 3-hydroxylase). Overexpression lines were evaluated for responses to stalk pathogens under greenhouse and field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 96 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…bmr lines) can provide the same level of or higher resistance to Fusarium spp. and Macrophomina phaseolina than sorghum lines with normal lignin content (Funnell-harris et al , 2010, 2014, 2017, 2018, 2019). This might be due to the inhibition the infection of stalk rotting pathogens by cell-wall-bound phenolic compounds from monolignol biosynthesis that can induce defensible pathways (Funnell-harris et al , 2017).…”
Section: Discussionmentioning
confidence: 90%
“…bmr lines) can provide the same level of or higher resistance to Fusarium spp. and Macrophomina phaseolina than sorghum lines with normal lignin content (Funnell-harris et al , 2010, 2014, 2017, 2018, 2019). This might be due to the inhibition the infection of stalk rotting pathogens by cell-wall-bound phenolic compounds from monolignol biosynthesis that can induce defensible pathways (Funnell-harris et al , 2017).…”
Section: Discussionmentioning
confidence: 90%
“…The results suggested that heterologous expression of AtMYB61 in rice increased the lignin content mainly by enriching S units as well as p-coumarate and tricin moieties in the lignin polymers 17) . Studies with S. bicolor aiming to increase energy content in biomass plants were also reported; lignin content was augmented by overexpression of a S. bicolor transcriptional activator, SbMYB60, in Sorghum 38,39) . In addition, lignin content of 30 Indonesian S. bicolor accessions was analyzed and high lignincontent accessions were identified 13) .…”
Section: Augmentation Of Lignin Contentmentioning
confidence: 99%
“…These strategies to increase lignin content and simplify lignin structures are also applicable to large-sized grass biomass plants, such as Sorghum, Panicum (switchgrass), Miscanthus and Erianthus. Recently, an increase in the energy content in biomass plants was achieved by the manipulation of S. bicolor F5H (CAld5H) expression 40) as well as the lignin content augmentation by SbMYB60 overexpression in S. bicolor 38,39) and isolation of high-lignin content S. bicolor accessions 13) .…”
Section: Simplification Of Lignin Structuresmentioning
confidence: 99%